Critical behaviour of conﬁned systems - Chalyi, A.V.; Chalyi, K.A.; Chernenko, L.M.; Vasilev, A.N. (Condensed Matter Physics, 2000)
The critical phenomena and peculiarities of phase transitions in the conﬁned ﬂuid systems are investigated. A system with the geometry of a planeparallel layer is chosen in order to discuss the inﬂuence of the space limitations on the critical characteristics of ﬂuids. The main ideas of the Munster iteration procedure were used to ﬁnd the pair and the direct correlation functions. Such an important characteristic of the system as the correlation length was found and correspondent results were analyzed in the terms of the scaling theory. Special attention is paid to the calculation of the shifts of the critical parameters (critical temperature and density). The three-moment approximation is used to investigate anisotropic liquids. The system of the Ornstein-Zernike (OZ) integral equations is involved to investigate the correlative properties of the binary ﬂuid mixtures. It is shown for the ﬂuids with the isomorphic character of the interaction that the approximation may be used that makes the system similar to the OZ one- component liquid model. The asymptotic formulae for the pair correlation functions are found and the validity of the Munster method for the binary mixtures is considered. The peculiarities of critical light opalescence for the systems with the special geometry are considered.